The Role of Evaluative Tools in the Creation of the Memorial Media Portrait of Jacques Chirac (1932—2019) - E. N. Mikhailova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the study of evaluative tools used in modern French media in order to form the media image of a representative of the political elite. The techniques used in the creation of a memorial media portrait of Jacques Chirac (1932—2019), President of France from 1995 to 2007 are considered. The research material was the most prestigious French print media of various political orientations, published in late September — early October 2019 in connection with the death of the ex-President of the French Republic. The relevance of the research topic is dictated by the close attention of modern linguistics to axiological phenomena, differently presented in different types of discursive practices. The novelty of the study is due to the appeal to the analysis of the complex of evaluation tools used in the French print media when characterizing the former leader of the state during the nation’s farewell period. The estimated potential of the title of the article and its influence on the formation of the estimated vector of the entire text of the publication are shown. A systematic analysis of the assessment expression means, reflected in the memorial media portrait of the politician, is given. The factors that influenced the peculiarities of their use in this type of media portrait are revealed.